Analisis Kegiatan Bongkar Muat Batu Bara pada Kapal MV. Chang Long terhadap Efisiensi Waktu Clearance IN & OUT di PT. Adhika Samudera Jaya - Hafid Ainul Yakin; Romanda Annas Amrullah; Teguh Pribadi; Trisnowati Rahayu (BADAN PENERBIT STIEPARI PRESS, 2025)
Ship loading and unloading activities are one of the vital components in port operations that greatly affect logistics efficiency and the smooth distribution of goods, especially energy commodities such as coal. This study aims to analyze the effect of coal loading and unloading activities on the MV. Chang Long ship on the efficiency of clearance in & out time at PT. Adhika Samudera Jaya, a shipping company that acts as a ship agent in the Palembang area. This clearance process includes administrative and operational aspects that must be fulfilled by the ship before and after loading and unloading activities are carried out. The study used a qualitative descriptive approach with data collection techniques through field observations, interviews with related parties such as operational heads, operational staff, and shippers, as well as documentation. The results of the study showed that there were several obstacles in loading and unloading activities that had a direct impact on delays in clearance in & out, including late payment of Letter of Credit (LC) by buyers, bad weather conditions, lack of coordination between related parties, and technical disruptions such as damage to loading and unloading equipment. These delays have an impact on operational cost inflation and decreased time efficiency. The solutions offered include document digitalization, improved communication and coordination between ship agents, ports, and buyers, and strengthening the logistics management system. This research is expected to be a reference for the shipping industry in managing loading and unloading activities effectively, as well as assisting port agencies in improving the efficiency of ship clearance procedures. With coordinated and systematic implementation, the clearance in & out process can take place faster, more efficiently, and have a positive impact on the smooth distribution of strategic commodities.